Differences in hip–knee joint coupling during gait after anterior cruciate ligament reconstruction. (February 2016) - Gribbin, Timothy C.; Slater, Lindsay V.; Herb, C. Collin; Hart, Joseph M.; Chapman, Ryan M.; Hertel, Jay; Kuenze, Christopher M.
Abstract: Background: After anterior cruciate ligament injury, patients have increased risk for developing degenerative osteoarthritis, potentially due to the kinematic changes that persist after surgical reconstruction. Current research only describes single joint kinematic differences rather than the way in which two joints behave concurrently, termed joint coupling. The purpose of this study was to compare knee motion relative to hip motion in anterior cruciate ligament reconstructed and healthy limbs during walking and jogging. Methods: Thirty-seven recreationally active volunteers (22 reconstructed, 15 healthy) walked and jogged at 4.83 km/h and 9.66 km/h respectively. Vector coding methods were used to calculate stride-to-stride variability, magnitude, and vector angle of 6 joint couples during walking and jogging: hip frontal–knee frontal planes, hip frontal–knee sagittal, hip frontal–knee transverse, hip sagittal–knee frontal, hip sagittal–knee transverse, and hip transverse–knee frontal planes. Findings: The hip sagittal–knee frontal and hip sagittal–knee transverse joint couples had decreased variability during mid-stance, and all other couples had increased variability during the stance phase in the reconstructed group. The reconstructed group had decreased magnitude of joint excursion in the hip frontal–knee sagittal couple during all phases of gait during walking. Vector angles of the hip frontal–knee transverse couple increased in the reconstructed group during the loading, middle, and terminal stance phases, and swing phase of gait during walking. Interpretation: The increased variability and decreased magnitude of joint excursion indicate that movement patterns were less consistent during walking gait despite employing a more constrained system during movement in the reconstructed limb compared to healthy controls. Highlights: We compared knee kinematic motion relative to the hip in healthy and anterior cruciate ligament reconstructed groups. We used vector coding methods to quantify stride-to-stride variability during gait. Anterior cruciate ligament reconstructed limbs exhibited decreased magnitude of joint excursion during walking. Anterior cruciate ligament reconstructed limbs displayed increased vector angles during walking gait. Aberrant gait patterns were noted in anterior cruciate ligament reconstructed limbs during the stance phase of gait.